1997
DOI: 10.12693/aphyspola.91.281
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Coupling and Magnetization Profiles of Binary and Ternary Magnetic Multilayers

Abstract: Within a spin-polarized LMTO approach in the atomic-sphere approximation we calculate ab initio the magnetic properties of various binary and ternary multilayers composed of Fe, Co, Ni, Cr, V and Cu. The emphasis lies on the indirect exchange interaction of the magnetic sandwiches across the antiferromagnetic or non-magnetic spacers, and on the profiles of the intrinsic resp. induced magnetic moments. Among other results we find (i) that Ni is very sensitive on its neighborhood and that (ii) at the interface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Our numerical values of Fe 3 V 5 can be compared to the LCAO and LMTO-ASA calculations of Moser et al [29] for the (001) (Fe 3 V 3 ) ∞ multilayers, who found 1.6 µ B for Fe at the interface, 2.8 µ B for the central Fe layer and −0.5 µ B for the interface V layer, close to our corresponding values, 1.77, 2.70 and −0.40 µ B , calculated inside the muffin-tin spheres. These results are similar to those obtained by the first-principles LMTO calculation of Süss et al [30]. The contribution from the interstitial region remains small and quite independent of the number of Fe layers.…”
Section: Spin and Orbital Moments Of Ideal Structuressupporting
confidence: 91%
“…Our numerical values of Fe 3 V 5 can be compared to the LCAO and LMTO-ASA calculations of Moser et al [29] for the (001) (Fe 3 V 3 ) ∞ multilayers, who found 1.6 µ B for Fe at the interface, 2.8 µ B for the central Fe layer and −0.5 µ B for the interface V layer, close to our corresponding values, 1.77, 2.70 and −0.40 µ B , calculated inside the muffin-tin spheres. These results are similar to those obtained by the first-principles LMTO calculation of Süss et al [30]. The contribution from the interstitial region remains small and quite independent of the number of Fe layers.…”
Section: Spin and Orbital Moments Of Ideal Structuressupporting
confidence: 91%
“…Already the second V layer, however, is practically nonmagnetic. These results are similar to those obtained by the first-principles LMTO calculations of F. Süss, [18,19].…”
Section: Formalismsupporting
confidence: 89%
“…In Fig. 2 we find that the main part (∼ 2/3) of the last-mentioned reduction is due to Ni, which is rather sensitive to changes of position and neighbourhood effects, see [19], although the Co moments, too, are weakened roughly by 2/5 of the reduction of Ni moments. In contrast, in a Co 4 /Cu n multilayer the internal Co-Co coupling seems to make the Co system rather stiff with respect to changes of the spacer thickness n, see the dashed curve in Fig.…”
mentioning
confidence: 74%
“…To test the influence of the interface on the exchange coupling extrema we have carried out SP-LMTO-ASA supercell band calculations for Co 4 /Cu n and NiCo 2 Ni/Cu n fcc-(001) multilayers. Our method, when applied to the Co 2 /Cu n and Co n /Cu 2 systems for n = 1, ..., 4, [7,8], and for other systems [19], has already proved to reproduce well both the overall behaviour of the exchange coupling with thickness-changes of the ferromagnetic slab and/or of the spacer, and also the moment profiles across the multilayers (including a small, but significant spacer spin polarization [8], as already mentioned). Although the exchange coupling amplitudes, when assumed to be proportional to the energy difference between the parallel and antiparallel configurations, would be one order of magnitude too large with our calculations, which unfortunately seems to be typical, at present, for ab-initio calculations of the present kind in our field (see [7] and comments therein), it is encouraging that the crossover thicknesses between the two configurations as well as the J oscillation period lengths from our results do compare favourably with experiments.…”
mentioning
confidence: 99%